Research on the Bearing Characteristics of Folding Steel Arch Frames with Different Snap-Fit Types Based on the Compensation Excavation Concept - Shaohua Li; Changfu Huang; Xiaojie Yang; Zhigang Tao; Jiaqi Guo; Humin Li; Tiejun Yao; Jie Hu (Buildings)
As the core technology for mechanized installation of tunnel folding steel arch frames, snap-fit connection optimization proves critical in enhancing the load-bearing efficiency of support systems and addressing surrounding rock deformation and instability caused by excavation-induced stress redistribution. Addressing the theoretical gaps in existing research regarding snap-fit selection mechanisms and quantitative evaluation criteria, this study adopts a combined approach of numerical simulation and field monitoring verification based on the excavation compensation concept to systematically investigate the load-bearing characteristics of folding steel arch frames with different snap-fit configurations. Key findings include (1) identification of 20 mm as the optimal joint diameter, where the vertical displacements of Type A and B snap-fit connections reached their minimum values of 43.1 mm and 39.2 mm, respectively; (2) demonstration of significant geometric configuration effects on principal stress distribution, with Type B connections exhibiting 4.5% lower maximum principal stress compared to Type A, effectively mitigating stress concentration; and (3) field monitoring data verification, revealing that Type B connections achieved 15.8% lower stress values than Type A at critical crown sections, satisfying yield strength requirements while demonstrating enhanced resistance to surrounding rock deformation induced by excavation-induced geostress redistribution. These results confirm Type B snap-fit connections as superior structural solutions for folding steel arch frames, thereby facilitating the advancement of mechanized installation technology for tunnel steel arch frames.